Revitalizing Growth Strategies: Enhancing Market Position for PT Sentra Food Indonesia - Faisa, Muhammad Idzhar (Economics and Business Journal (ECBIS), 2025)
This study aims to analyze the strategic management of PT Sentra Food Indonesia using a SWOT analysis to identify key internal and external factors. Employing a descriptive qualitative approach, the research utilizes IFAS and EFAS matrices to evaluate the company's strengths, weaknesses, opportunities, and threats. The analysis includes an examination of the company's brand, distribution network, market reach, and supplier dependencies, using data from company records and industry reports. The findings reveal PT Sentra Food Indonesia's robust brand and distribution network but highlight challenges such as limited market reach and supplier reliance. Opportunities for growth are identified in product innovation, market expansion, and digital transformation. These insights provide recommendations for enhancing the company's sustainability and competitiveness in the dynamic food industry.